2019
DOI: 10.1097/wnf.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Concentrations of Nimodipine Correlate With Long-term Outcome in Aneurysmal Subarachnoid Hemorrhage: Pilot Study

Abstract: Objectives The aim was to evaluate plasma and cerebrospinal fluid (CSF) nimodipine concentrations in patients with aneurysmal subarachnoid hemorrhage and their correlation with clinical outcome. Methods Nimodipine infusion was started at 1 mg/h and increased up to 2 mg/h and continued up to 21 days in surviving patients. Arterial and CSF samples were collected at least after 24 hours of stable nimodipine dosing. Delayed cerebral ischemia and vasospasm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Therefore, it is not clear if all patients are getting the full benefit of nimodipine using a fixed dose regimen and the evidence supporting a correlation between nimodipine concentrations and patient outcomes is scarce and not clear. Riva et al have reported an association between nimodipine CSF concentrations and neurological outcomes at 9 months following SAH onset but they were unable to find such correlation with plasma concentrations [62]. It should be noted, however, that all patients were dosed using nimodipine IV infusion and their plasma concentrations ranged from 24.9 to 71.8 ng/ mL, concentrations way above what has been reported in some patients given oral dosing [23,56].…”
Section: Nimodipine Exposure and Outcomes Following Sahmentioning
confidence: 85%
“…Therefore, it is not clear if all patients are getting the full benefit of nimodipine using a fixed dose regimen and the evidence supporting a correlation between nimodipine concentrations and patient outcomes is scarce and not clear. Riva et al have reported an association between nimodipine CSF concentrations and neurological outcomes at 9 months following SAH onset but they were unable to find such correlation with plasma concentrations [62]. It should be noted, however, that all patients were dosed using nimodipine IV infusion and their plasma concentrations ranged from 24.9 to 71.8 ng/ mL, concentrations way above what has been reported in some patients given oral dosing [23,56].…”
Section: Nimodipine Exposure and Outcomes Following Sahmentioning
confidence: 85%
“…None of those studies, however, has reported a correlation between reduced exposure and patient outcomes. Riva et al have reported an association between nimodipine cerebrospinal fluid concentrations and neurological outcomes at 9 months following SAH onset but they were unable to find such correlation with plasma concentrations (14). It should be noted, however, that all their patients were dosed using nimodipine IV infusion and their plasma concentrations ranged from 24.9 to 71.8 ng/ml, concentrations way above what has been reported in patients given oral dosing (17,19).…”
Section: Discussionmentioning
confidence: 80%
“…It is not clear, however, whether this technique of administration result in reduced clinical effectiveness and in turn poor outcomes. Although the evidence supporting a correlation between nimodipine plasma concentrations and patient outcomes is scarce and not clear, lack of absorption definitely denies the benefits of any drug used systemically (14). Therefore, the present study aimed to answer the following research question: Among SAH patients, is taking nimodipine by enteral feeding tube associated with worse outcomes compared to those who swallow nimodipine whole tablets?…”
Section: Introductionmentioning
confidence: 98%
“…It can cross the BBB and enter the CNS [197]. A recent study has demonstrated a direct correlation between the concentration of nimodipine in cerebrospinal fluid, but not in arterial blood, and the disease outcome after subarachnoid hemorrhage [198]. These data may indicate a protective effect of nimodipine.…”
Section: Dhpmentioning
confidence: 99%